High-frequency chromosome transfer in Rhodopseudomonas sphaeroides promoted by broad-host-range plasmid RP1 carrying mercury transposon Tn501. - Pemberton, J M (1981)
Insertion of the mercury resistance transposon Tn501 into broad-host-range plasmid RP1 greatly enhanced the ability of this plasmid to promote chromosome transfer in the photosynthetic bacterium Rhodopseudomonas sphaeroides. Compared with the wild-type RP1, which produced less than 10(-8) recombinants per donor cell, RP1::Tn501 produced between 10(-3) and 10(-7) recombinants per donor cell depending upon the marker selected. Plasmid RP1::Tn501 promoted polarized transfer of the chromosome from one or perhaps two origins on the chromosome, giving rise to two linkage groups. All of the biosynthetic and antibiotic resistance genes that have been mapped, including those involved in photosynthesis, occur on one or another of these linkage groups.